An indigenous knowledge-based sustainable landscape for mountain villages: The Jiabang rice terraces of Guizhou, China. (May 2021) - Wang, Nian; Fang, Ming; Beauchamp, Michelle; Jia, Ziyu; Zhou, Zhengxu
Abstract: A robust understanding of the effect of indigenous knowledge systems (IKSs) on spatial patterns of natural resource management (NRM) in mountain landscapes could contribute to fostering ecological sustainability and cultural diversity. This study addresses the mechanisms by which IKSs influence landscape through the management of various natural resources. Data was collected through multiple methods: in-depth interviews, a questionnaire survey, and spatial participatory mapping, in Jiabang region, Guizhou China. The results show that 1) local rice farming methods and livelihoods have influenced and been influenced by the creation and application of IKSs including resource management knowledge of the mountains, forests, water and agricultural resources; 2) the systems have shaped the communities' landscape and the resulting spatial diversity through the interlocking mediation of NRM with IKSs. This study also shows that IKSs continue to be transmitted well to the following generation. Based on these findings, the mechanism of the influence of IKSs on landscapes through NRM was discussed, and an ideal diagram of the sustainable landscape of the rice terraces was proposed. This research can provide reference to the sustainable resource use, mountain protection, and tourism for mountainous agricultural community.